Analisis Pengaruh Kompetensi Profesional dan Iklim Organisasi Terhadap Kinerja Dosen STIE Rahmaniyah Sekayu (Jurnal Manajemen dan Investasi (MANIVESTASI), 2019)
ABSTRACTÂ This study aims to determine the effect of professional competence and the organizational climate of lecturers simultaneously and partially on the performance of STIE Rahmaniyah Sekayu lecturers. The data used primary data from the results of distributing questionnaires to 49 respondents, namely lecturers of management study programs and accounting study programs at STIE Rahmaniyah Sekayu. Data analysis techniques used multiple linear regression analysis. The results of the study indicate that the simultaneous professional competence and organizational climate influence the performance of lecturers by 0,000